The politics of vulnerable masculinity in couple therapy. - Smoliak, Olga; LaMarre, Andrea; Rice, Carla; Tseliou, Eleftheria; LeCouteur, Amanda; Myers, Madison; Vesely, Leslie; Briscoe, Cara; Addison, Maggie; Velikonja, Linnea (Journal of Marital & Family Therapy, 2022)
Couple therapy and related literature has problematized men's emotional inexpressiveness as constraining for men and as contributing to men's privileged and dominating position vis‐à‐vis women. Fostering men's emotionality in and outside of therapy has been proposed as a way to improve men's well‐being and relationships and promote gender equality. Critical masculinity scholars have noted that many men now enact vulnerable ("softer") and emotional forms of masculinity. Yet, there is lack of insight into how such enactment may intersect with gender inequality. This article presents a critical thematic analysis of 30 transcribed videotaped couple therapy sessions focusing on the performance of men's affective masculinities and the political dimensions of men's increasing emotionality within couple therapy. The study shows that vulnerable masculinities, although argued as bearing the potential to foster relational and social change, may also obscure continuing commitment to dominant masculinity norms. Implications for practice are discussed.